Study Relates To Village Government Management - Ermi Triaji (Dinasti Publisher, 2023)
Increasing the performance of village government could be important thing to do in order to improve the benefits which felt by the village communities from the development of village. It feels essential to learn and deep explore regarding the management functions of village government itself, which seems less effective to generate huge results and benefits for its community. Qualitative method has been chooses as research method by the use of case study approach, through selected some cases which occurred relates to effectiveness of village government management in four villages (Nagrog Village, Samida Village, Leles Village, Kiarajangkung Village). Based on this research results, it is found that, there are 5 propositions results, namely Village government management is less than effective and did not fulfill management rules and functions properly, there are obstacles to Implementing management functions in village government’s managerial activities, there are also barriers in performance which hinder to achieve the goal of village government in four villages, therefore need proper strategy to increase the effectiveness of village government management in an effort to improve its performance as well as strategy to increase the efficacy of village government in improving its performances.